FRI0370 Development of Two Novel Patient Reported Outcome (PRO) Measures: The Systemic Lupus Erythematosus (SLE) Symptom Severity Diary (SSD) and Sle Impact Questionnaire (SIQ). (9th June 2015) - Mathias, S.D.; Berry, P.; deVries, J.; Askanase, A.; Pascoe, K.; Colwell, H.; Chang, D.
Abstract : Background: SLE symptoms can vary from day-to-day; current PRO measures are inadequate to capture daily symptom variability in a research setting. Objectives: To develop two PROs for use in clinical research, suitable for patient completion at home using an electronic format (ePRO), to assess: 1) SLE symptoms; and, 2) SLE impact. Methods: Following IRB approval, 6 US rheumatology practices enrolled SLE patients for face-to-face concept elicitation (CE) interviews about SLE. The SLE Symptom Severity Diary (SSD) and SLE Impact Questionnaire (SIQ) were drafted and cognitively debriefed (CD) with SLE subjects to evaluate content, clarity, and relevance. The tools were finalized following clinical input and a translatability assessment. Results: 41 subjects completed CE interviews (95% female, 55% Caucasian, 25% African American, mean age 48 years, 46% with moderate/severe SLE). Common symptoms included fatigue (98%), joint pain (93%), rash (88%), joint stiffness (80%), swelling of feet/hands (80%), and cognitive/memory issues (63%). Subjects reported difficulty with chores/housework (61%), leisure activities (39%), driving (39%), and sleeping (39%). Concepts most frequently impacting functioning are summarized below. Eighteen subjects completed CD interviews (94% female, 61% African American, 39% Caucasian, mean age 51 years, 50% with moderate/severe SLE). Minor revisions were made for emphasis and redundant items were deleted based on the CD interviews. The final SSD contains 17 common SLE symptoms, uses an 11-point response scale ("0 = Absent/Did not have" to "10 = Worst Imaginable"), and a 24-hour recall period. The final SIQ contains 50 items with a 7-day recall and 5-point Likert response options ("Not At All" to "Very Much"), assessing ability to make plans, take care of yourself/others, leisure activities, social functioning, physical functioning, sleep, memory/cognitive issues, work, and emotional functioning. Conclusions: The SSD and SIQ are comprehensive PRO questionnaires that may be useful to evaluate fluctuating patient symptoms and their impact on SLE patients' lives. Measurement properties will be assessed in the near future. Acknowledgements: The research presented in this abstract was funded by GlaxoSmithKline, USA. Disclosure of Interest: S. D. Mathias Consultant for: GlaxoSmithKline, P. Berry Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, J. deVries Shareholder of: GlaxoSmithKline, A. Askanase Consultant for: GlaxoSmithKline, K. Pascoe Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline, H. Colwell Consultant for: GlaxoSmithKline, D. Chang Shareholder of: GlaxoSmithKline, Employee of: GlaxoSmithKline